2020
DOI: 10.1007/s10198-020-01249-x
|View full text |Cite
|
Sign up to set email alerts
|

Real-world study of direct medical and indirect costs and time spent in healthcare in patients with chronic graft versus host disease

Abstract: Chronic graft versus host disease (cGVHD) is a debilitating and costly complication following haemopoietic stem cell transplantation (HSCT). This study describes the economic burden associated with cGVHD. Direct costs associated with specialised healthcare utilisation (inpatient admissions and outpatient visits), as well as indirect costs associated with sickness absence-associated productivity loss were estimated in patients who underwent allogeneic HSCT in Sweden between 2006 and 2015, linking population-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…GvHD also has a significant impact on healthcare resource utilisation, with patients experiencing more and longer hospitalisations and incurring greater healthcare costs [39][40][41][42]. A study in the USA found significantly greater 1-year post-alloHSCT costs for patients with aGvHD compared to those without aGvHD ($466,720 vs. $263,568; P < 0.001), with inpatient care being the primary cost driver [43].…”
Section: Key Pointsmentioning
confidence: 99%
See 3 more Smart Citations
“…GvHD also has a significant impact on healthcare resource utilisation, with patients experiencing more and longer hospitalisations and incurring greater healthcare costs [39][40][41][42]. A study in the USA found significantly greater 1-year post-alloHSCT costs for patients with aGvHD compared to those without aGvHD ($466,720 vs. $263,568; P < 0.001), with inpatient care being the primary cost driver [43].…”
Section: Key Pointsmentioning
confidence: 99%
“…Mortality with GvHD Percentage of GvHD patients developing refractory GvHD aGvHD 39% with sibling donors [24] 12% grade II [25] 91% 100-day overall survival (OS) grade II [32] 16.2% aGvHD (5.3% without GvHD) [28] 36% grade II-IV steroidrefractory aGvHD [25] 59% with unrelated donors [24] 11-16% grade III-IV [25,31] 65% 100-day OS grade III-IV [32] 8-16% [35] 49% [25] 86% 1-year OS grade III-IV [33] 49% grade IV aGvHD 35% TRM (11% without cGvHD) [29] 31% all grades steroidrefractory [25] 37% [25] 8% grade 3 [25] 53% 3 years OS [26] 8-11% 3-year mortality [35] 45% 5 years OS [26] with moderate-to-severe cGvHD were approximately fourfold higher than for patients without cGvHD [41].…”
Section: Survival With Gvhd By Gradementioning
confidence: 99%
See 2 more Smart Citations
“…To address this unmet need, we used national registers to perform a retrospective, population-based longitudinal study. Instead of the NIH method based on the presentation of cGVHD, we used our newly introduced method [14] that considered the timing and extent of the immunosuppressive treatment given to HSCT recipients, with the objectives to investigate the burden of disease (including mortality and morbidities) and healthcare utilization in Sweden.…”
Section: Introductionmentioning
confidence: 99%